A real estate price index for Stockholm, Sweden 1818–2018: putting the last decades housing price boom in a historical perspective. Issue 1 (2nd January 2021) - Edvinsson, Rodney; Eriksson, Klas; Ingman, Gustav
ABSTRACT: Earlier research describes the development of real housing prices as a 'hockey stick', i.e. of long stagnation followed by a sharp upturn in recent decades. A problem is that there are very few indices of residential property covering longer periods. Using a database of around 10, 900 sales, this study presents a historical housing price index for Stockholm 1818–1875, which extend a previous index by 57 years, one of the longest for any city. A so-called repeated sales index is compared to a sales price appraisals ratio index. We show that in real terms there have been two long upswings, in 1855–1887 and 1993–2018. In other periods, real prices were stagnant or even slightly declining. The nineteenth century upturn did not end in a crash, but was followed by stagnation for a century. There are many similarities between the two upturns. For example, both coincided with the demographic expansion and were preceded by deregulations. During both periods, properties became more expensive relative income levels. Our new data, available at http://historia.se/StockholmResidentialPrices1818_1875.xlsx, reveals that the pattern of a 'hockey stick' between 1870 and 2012 is complemented by another hockey stick when the index is expanded.